2015
DOI: 10.14397/jals.2015.49.6.187
|View full text |Cite
|
Sign up to set email alerts
|

Contribution Analysis of Carcass Traits on Auction Price in Gyeongsangnam-do Hanwoo

Abstract: The aim of this study was to estimate the effect of sex, slaughtered season and year on carcass traits, and also estimated the corresponding effects of the contribution to auction and *

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…However, the mean BFT trait value was higher than that reported earlier. The present findings were in corroboration with the findings of Sun et al (2010) and Park et al (2015), who showed that BFT in slaughtered Hanwoo was higher in the winter. It is considered that Hanwoo can maintain their body temperature in the Gangwon region where the annual average temperature is generally low and the daily temperature range is extremely wide.…”
Section: Resultssupporting
confidence: 93%
“…However, the mean BFT trait value was higher than that reported earlier. The present findings were in corroboration with the findings of Sun et al (2010) and Park et al (2015), who showed that BFT in slaughtered Hanwoo was higher in the winter. It is considered that Hanwoo can maintain their body temperature in the Gangwon region where the annual average temperature is generally low and the daily temperature range is extremely wide.…”
Section: Resultssupporting
confidence: 93%
“…Lee et al [3] reported that the auction price had 0.73 of the highest correlation with the marbling score, and the carcass price had 0.71 and 0.61 of correlation with the carcass weight and the marbling score, respectively. Similarly, marbling accounted for 95.4% of the auction price (R 2 = 0.51), and 52.6% and 44.3% of the total price were attributable to marbling and carcass weight (R 2 = 0.75), respectively [30]. Consequently, marbling and carcass weight were the most contributory factors among carcass traits and therefore, it will be possible to determine the optimal price through effective balance between these two factors.…”
Section: Discussion On Identification Of Optimal Factors Based On Ecomentioning
confidence: 99%
“…Before dapsone was identified as an inflammasome competitor, clinicians used it as an adjuvant [15], alternative [16], augmentation [17,18], or active ingredient [19,20]. Dapsone has been used as a therapeutic agent for mild cognitive impairment [9,21], AD [14], PD [22,23], seizures [24], strokes [13,25,26], and finally, COVID-19 ARDS [6,27].…”
Section: Evidence From Brain Diseasesmentioning
confidence: 99%